2008
DOI: 10.1007/s11999-008-0424-z
|View full text |Cite
|
Sign up to set email alerts
|

Stemmed Implants Improve Stability in Augmented Constrained Condylar Knees

Abstract: We previously combined experimental and computational measures to ascertain whether tibial stem augmentation reduces bone strains beneath constrained condylar implants. Using these same integrated approaches, we examined the benefit of a stem when a wedge is used. Implants were removed from the eight paired cadaver specimens from our previous experiment, and oblique defects created that were restored with 15°metallic wedges cemented in place. We applied a varus moment and an axial load and monitored relative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
2
26
0
1
Order By: Relevance
“…We recommend the use of at least two screws for initial stability of the graft and to achieve compression at the graft host bone interface. Rawlinson et al ., in their cadaveric study, concluded that the use of stem extenders improves knee stability by reducing bone stresses and micromotion between the implant and the adjacent bone 16. We also recommend and prefer to use stem extenders in all our cases.…”
Section: Discussionmentioning
confidence: 76%
“…We recommend the use of at least two screws for initial stability of the graft and to achieve compression at the graft host bone interface. Rawlinson et al ., in their cadaveric study, concluded that the use of stem extenders improves knee stability by reducing bone stresses and micromotion between the implant and the adjacent bone 16. We also recommend and prefer to use stem extenders in all our cases.…”
Section: Discussionmentioning
confidence: 76%
“…When tibia plateau has peripheral bone defects, various surgical options can be used for handling such defects in TKA including: prosthetic augments – using metal wedges, custom made prostheses, and spacer to fill the defect; autograft – correcting the defect through bone grafting with autogenous bone; allograft – using allograft reconstruction of the defect; and cement – filling the defect with bone cement or using bone cement reinforced with buttressing screws 1–6 …”
Section: Discussionmentioning
confidence: 99%
“…This bone deficiency may be reconstructed in various ways such as with bone graft, screws, and cement, bone bag technique or commercially available metal tibial tray augments 1–6 . Current surgical opinion holds that when tibial tray augments are used then stem augmentation of the tibial tray is also routinely required for construct stability 2,3,5,7–10 . However, there has been little in the way of published data to support this position and further this approach may not be routinely necessary for all tibial tray designs.…”
Section: Introductionmentioning
confidence: 99%
“…Bár a press fi t rögzí-tési módszer élettani el nyei ismeretesek, biomechanikai kísérletek alapján több tanulmány a cementezett rögzítés mellett foglal állást. Cementes rögzítés esetén terhelés hatására szignifi kánsan kisebb mikromozgások észlel-het k, mint press fi t rögzítés esetén 18,19,20,21 .…”
Section: A Protézis Rögzítése éS a Rögzítés Biomechanikájaunclassified